2013
DOI: 10.1111/1460-6984.12059
|View full text |Cite
|
Sign up to set email alerts
|

Impact of placement type on the development of clinical competency in speech–language pathology students

Abstract: Article titleImpact of placement type on the development of clinical competency in speech language pathology students AbstractBackground: Speech language pathology students gain experience and clinical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 53 publications
1
27
0
2
Order By: Relevance
“…Prescriptiveness about placement and patient types denies what we know about the generalisability and transferability of knowledge and skills. For example, Sheepway, Lincoln and McAllister (2014) studied the development of student competence in speech language pathology degree students and found that their competencies developed over a one year period of clinical placements irrespective of placement type or context or intensity of placement (daily versus block mode) thus indicating that there was a possible transfer of learning occurring between placement types.…”
Section: Prescriptivenessmentioning
confidence: 99%
“…Prescriptiveness about placement and patient types denies what we know about the generalisability and transferability of knowledge and skills. For example, Sheepway, Lincoln and McAllister (2014) studied the development of student competence in speech language pathology degree students and found that their competencies developed over a one year period of clinical placements irrespective of placement type or context or intensity of placement (daily versus block mode) thus indicating that there was a possible transfer of learning occurring between placement types.…”
Section: Prescriptivenessmentioning
confidence: 99%
“…Students were drawn from the undergraduate program and some from the Masters of SLP program, representing differences in maturity, background knowledge, and experience. Although the students' prior knowledge and experiences were not explored in this study, it is plausible that their ability to generalise prior learning across clinical settings and placements presented a challenge for them (Sheepway, Lincoln, and McAllister 2014). This aspect of competence is particularly important in the context of increased demand for placements, where it may not be possible for education providers to expose students to all clinical populations and recognition of transferrable knowledge and skills is essential.…”
Section: Discussionmentioning
confidence: 98%
“…Firstly, SLP students are never placed on year-long clerkships (Sheepway, Lincoln, and McAllister 2014); the SLP placements provided were 24 days long, over 6 or 8 weeks depending on the university placing the students. This study did not examine the potential effects of the different duration of the placement on the outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Individual universities can enter into formal agreements with other universities to share data . This has allowed the development of large scale research projects on the development of competence in different types of students, the impact of placement types on competence development 22 and the impact of different curricula models 23 (e .g ., traditional vs problem based learning; 4 year bachelor vs 2 year graduate entry masters) on the trajectories of competence development .…”
Section: Assessment Of Students' Competency On Practicum: Competency mentioning
confidence: 99%